2007
DOI: 10.1177/0040517507074816
|View full text |Cite
|
Sign up to set email alerts
|

Odor Intensity in Apparel Fabrics and the Link with Bacterial Populations

Abstract: Nine apparel fabrics varying in fiber (cotton, wool, polyester) and knit structure (1 × 1 rib, interlock, single jersey) were investigated for their retention of axillary odor following wear. As axillary odor results from bacterial metabolism of apocrine and sebaceous secretions, counts of total aerobic bacteria and corynebacteria on the fabrics were carried out. Odor intensity was strongly associated with the fiber type, with polyester fabrics rating high in odor intensity and cotton and wool mid-low odor int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 23 publications
6
78
2
Order By: Relevance
“…It is generally accepted that the choice of clothing has an impact on malodor formation (10). This research showed that polyester clothes create a significantly higher malodor compared to cotton clothing after a fitness session and an incubation period.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…It is generally accepted that the choice of clothing has an impact on malodor formation (10). This research showed that polyester clothes create a significantly higher malodor compared to cotton clothing after a fitness session and an incubation period.…”
Section: Discussionmentioning
confidence: 77%
“…Dravniek et al (9) refers to this as the primary odor, originating from the axilla itself, and the secondary odor, originating from clothing in contact with the axilla. The odor would then differ between the two sites (10). It is found that a stronger body odor is generated by wearing synthetic clothing textiles compared to natural textiles (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Axillary odor following wear is lowest on wool, followed by cotton-based fabrics and highest on polyester [53]. It has even been shown in tests that the odor on polyester fabrics can increase up to a week after the garments was used, which did not happen with wool or cotton specimens [54].…”
Section: Inherent Fiber Soiling Propertiesmentioning
confidence: 96%
“…Bowers & Chantrey [16] note that these oils are more difficult to remove from polyester than from cotton. These oily contaminations also serve as a nourishing medium on which microorganisms thrive, leading to the development of malodor in clothing [17,[19][20][21]. Malodor that originates in textiles is secondary in nature as it is a resultant product of bacterial action on sweat and human skin secretions McQueen et al [20].…”
Section: Introductionmentioning
confidence: 99%